Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network Update: October, 2023 – April, 2024 ... - Campbell, Sandy (University of Alberta Library, 2024)
This article reports activities of the University of the Arctic Decolonization of Arctic Library and Archives Metadata (DALAM) Thematic Network for October 2023 - April 2024. ...